Real-time weakness of the global economy: A first assessment of the coronavirus crisis - Danilo Leiva-Leon; Gabriel Pérez-Quirós; Eyno Rots (European Central Bank (ECB), 2020)
We propose an empirical framework to measure the degree of weakness of the global economy in real-time. It relies on nonlinear factor models designed to infer recessionary episodes of heterogeneous deepness, and fitted to the largest advanced economies (U.S., Euro Area, Japan, U.K., Canada and Australia) and emerging markets (China, India, Russia, Brazil, Mexico and South Africa). Based on such inferences, we construct a Global Weakness Index that has three main features. First, it can be updated as soon as new regional data is released, as we show by measuring the economic effects of coronavirus. Second, it provides a consistent narrative of the main regional contributors of world economy's weakness. Third, it allows to perform robust risk assessments based on the probability that the level of global weakness would exceed a certain threshold of interest in every period of time.
Keywords: E32; C22; E27; 330; International; Business Cycles; Factor Model; Nonlinear